Low Voltage Converter for Organic Tranducers in Energy Harvesting - Znbill, Laila (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
The paper describes the possibilities of energy harvesting using organic semiconductors. It is shown that organic semiconductors enable a large variability and some of their properties may be better than by inorganic semiconductor materials. Simple and reliable JFET driven DC to DC converter was designed for low voltage applications as thermoelectric generators and single-cell solar panels. It is able to operate from the voltage of few tenths of Volt and the output voltage could be in the level of several Volts. The efficiency was found close to 50%. Material and production costs are significantly lower than in case of standard low power integrated circuits.
Keywords: Organic semiconductors; Energy harvester; low power DC/DC converter